Electronic origins of structural distortions in post-transition metal oxides: Experimental and theoretical evidence for a revision of the lone pair model - WATSON, GRAEME WILLIAM (My University, 2006)
Structural distortions in post-transition metal oxides are often explained in terms of the influence of sp hybrid "lone pairs." Evidence is presented here showing that this model must be revised. The electronic structures of prototypically distorted ?-PbO and ?-Bi2O3 have been measured by high-resolution x-ray photoemission and soft x-ray emission spectroscopies. In contrast with the expectations of the lone pair model, a high density of metal 6s states is observed at the bottom of the valence band. The measurements are consistent with the results of density functional theory calculations
PUBLISHED
Keywords: density functional theory; density functional theory